A flame retardant and anti-drip bio-polyester material and its preparation method and application
By using a composite flame retardant of Co-MOF charging agent, epoxy modified tannin and ammonium polyphosphate in biopolyester materials, the problem of droplets during combustion of biopolyester materials is solved, while significantly improving its flame retardant performance and maintaining mechanical properties.
Patent Information
- Application Number
- CN202410793075.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-06-19
AI Technical Summary
Biopolyester materials have serious problems with droplets during combustion, and commonly used flame retardants will release toxic gases, affecting the environment and health. It is difficult for the prior art to significantly improve their flame retardant and droplet resistance while maintaining mechanical properties.
Using a composite flame retardant, composed of Co-MOF carbonizing agent, epoxy modified tannin acid and ammonium polyphosphate, it is melt blended by a screw extruder or torque rheometer to prepare a biopolyester material with excellent flame retardant and droplet resistance.
The excellent flame retardant and droplet resistance of biopolyester materials are achieved while maintaining good mechanical properties. The synergistic effect of the new spherical flame retardant Co-MOF carbonizing agent and epoxy modified tannin significantly improves the flame retardant effect.
Smart Images

Figure CN118703032B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardant materials, and in particular to a flame retardant and anti-melting droplet bio-polyester material and a preparation method and application thereof. Background Art
[0002] Polyester materials derived from biomass resources, such as polylactic acid (PLA), polyglycolic acid (PGA), polyhydroxyalkanoate (PHA), polybutylene succinate (PBS), etc., have many advantages such as biodegradability, good biocompatibility, excellent mechanical properties, etc., and are widely used in packaging, biomedicine, textiles and many other fields. However, the thermoplastic polyester structure is extremely easy to burn in the air and is accompanied by serious molten dripping problems, which poses a great fire safety hazard during actual use. Therefore, it is of great significance to improve the flame retardant and anti-melting properties of biopolyester materials.
[0003] Adding flame retardants to bio-polyester materials is the most convenient and economical method for flame retardant modification. However, commonly used halogen flame retardants release toxic and harmful gases during combustion, which can cause serious harm to the natural environment and human health. These shortcomings limit their application in bio-polyester materials. In recent years, phosphorus-nitrogen flame retardant systems have attracted more and more attention from scholars due to their high efficiency and environmental protection.
[0004] Since there is a serious droplet problem during the combustion of bio-polyester materials, more flame retardants need to be added to solve the droplet problem. However, adding more flame retardants will lead to a decrease in the mechanical properties of bio-polyester materials, limiting their scope of application. Therefore, the development of phosphorus-nitrogen environmentally friendly flame retardants for bio-polyester materials can significantly improve their flame retardant and anti-droplet properties while maintaining their mechanical properties, which has important practical application value. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention provides a flame retardant and anti-melting droplet bio-polyester material and a preparation method and application thereof. The bio-polyester material of the present invention has excellent flame retardant and anti-melting droplet properties while maintaining good mechanical properties.
[0006] The technical solution of the present invention is as follows:
[0007] The first object of the present invention is to provide a flame retardant and anti-melting droplet bio-polyester material, the raw materials of which include 73-82wt% of polyester material and 18-27wt% of composite flame retardant;
[0008] The composite flame retardant is composed of Co-MOF carbonizing agent, epoxy-modified tannic acid and ammonium polyphosphate;
[0009] The proportions of Co-MOF carbonizer, epoxy-modified tannic acid and ammonium polyphosphate in the raw materials are 4-6wt%, 10-15wt% and 4-6wt%, respectively.
[0010] In one embodiment of the present invention, the polyester material is one or more of polylactic acid, polyglycolic acid, polyhydroxyalkanoate, and polybutylene succinate.
[0011] In one embodiment of the present invention, the preparation method of the Co-MOF carbonizing agent is:
[0012] 4-Formylbenzoic acid, p-phenylenediamine and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide react to generate a flame retardant organic ligand, which is then thermally reacted with a cobalt salt to obtain the product.
[0013] In one embodiment of the present invention, the molar ratio of 4-formylbenzoic acid, p-phenylenediamine and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 2-2.4:1:2-2.4.
[0014] Preferably, the molar ratio of 4-formylbenzoic acid, p-phenylenediamine and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 2-2.2:1:2-2.2.
[0015] In one embodiment of the present invention, the cobalt salt is cobalt nitrate hexahydrate; and the molar ratio of the flame retardant organic ligand to the cobalt nitrate hexahydrate is 3:1-2.
[0016] In one embodiment of the present invention, the Co-MOF carbonizing agent is spherical, and its specific preparation method is:
[0017] (1) Under an inert gas atmosphere, 4-formylbenzoic acid and a catalyst are dissolved in an organic solvent, and then p-phenylenediamine is dissolved in an organic solvent, and then added dropwise into the above reaction system at a reaction temperature of 60-80° C., and reacted for 6-12 hours; keeping the temperature unchanged, adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and continuing the reaction for 6-12 hours to obtain a flame retardant organic ligand.
[0018] (2) dispersing the flame retardant organic ligand obtained in step (1) in an organic solvent, adding ammonia water dropwise and stirring to obtain a uniform solution, adding cobalt nitrate hexahydrate and stirring evenly, and then transferring to a high-pressure reactor for solvent thermal reaction. After the reaction is completed, cooling to room temperature, centrifuging, washing, and drying to obtain a Co-MOF carbonizer.
[0019] In one embodiment of the present invention, in step (1), the inert gas is nitrogen.
[0020] In one embodiment of the present invention, in step (1), the organic solvent is anhydrous ethanol; and the catalyst is glacial acetic acid.
[0021] In one embodiment of the present invention, in step (1), the concentration of 4-formylbenzoic acid in the organic solvent is 0.3-0.5 mol / L, preferably 0.4 mol / L.
[0022] In one embodiment of the present invention, in step (1), the concentration of p-phenylenediamine in the organic solvent is 0.3-0.5 mol / L, preferably 0.4 mol / L.
[0023] In one embodiment of the present invention, in step (2), the organic solvent is one or more of anhydrous methanol, anhydrous ethanol, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0024] In one embodiment of the present invention, in step (2), the mass concentration of ammonia water is 23-25%, and the amount used is 30-40% of the mass of the flame retardant organic ligand.
[0025] In one embodiment of the present invention, in step (2), the molar ratio of the flame retardant organic ligand to cobalt nitrate hexahydrate is 3:2.
[0026] In one embodiment of the present invention, in step (2), the temperature of the solvent thermal reaction is 120-160° C., and the reaction time is 24-48 hours.
[0027] In one embodiment of the present invention, the epoxy-modified tannic acid is prepared by reacting epichlorohydrin with tannic acid.
[0028] In one embodiment of the present invention, the preparation method of the epoxy-modified tannic acid is as follows: in an inert gas atmosphere, tannic acid is dissolved in epichlorohydrin, a catalyst is added at a temperature of 70-80°C to react for 3-6 hours, the temperature is lowered to 50-60°C, an alkali reagent is added to continue the reaction for 3-6 hours, and after the reaction is completed, the product epoxy-modified tannic acid is obtained by washing, liquid separation, rotary evaporation, and drying.
[0029] In one embodiment of the present invention, the mass ratio of tannic acid to epichlorohydrin is 1:13.6-27.2.
[0030] Preferably, the mass ratio of tannic acid to epichlorohydrin is 1:13.6-20.4.
[0031] In one embodiment of the present invention, the catalyst is tetrabutylammonium bromide, and the amount used is 1-3% of the total mass of tannic acid and epichlorohydrin.
[0032] In one embodiment of the present invention, the alkaline reagent is a sodium hydroxide solution with a concentration of 30-40% and an amount of 5-10% of the total mass of tannic acid and epichlorohydrin.
[0033] The second object of the present invention is to provide a method for preparing a flame retardant and anti-drip bio-polyester material, comprising the following steps:
[0034] 73-82 wt% of polyester material and 18-27 wt% of composite flame retardant are added into a screw extruder or a torque rheometer for melt blending, and then a flame retardant and anti-melting droplet bio-polyester material is obtained through a molding process.
[0035] In one embodiment of the present invention, the temperature of melt blending is 140-240° C., and the time is 6-10 min.
[0036] The third object of the present invention is to provide an application of a flame retardant and anti-drip bio-polyester material for use in the fields of automobiles, textiles, transportation or electronic appliances.
[0037] The beneficial technical effects of the present invention are:
[0038] The flame retardant and anti-drip bio-polyester material of the present invention has excellent flame retardant and anti-drip properties. The new spherical flame retardant Co-MOF carbonizer introduces phosphorus and nitrogen flame retardant elements and can promote the polyester material to form a stable carbon layer, and has a relatively excellent flame retardant effect; the epoxy-modified tannic acid not only serves as an excellent carbon source but also has an anti-ultraviolet function; the three components of the new spherical flame retardant Co-MOF carbonizer, epoxy-modified tannic acid and ammonium polyphosphate can synergistically better exert the flame retardant effect.
[0039] The flame retardant and anti-melting droplet bio-polyester material of the present invention has relatively good mechanical properties. Under the condition of high addition amount of composite flame retardant, the excellent compatibility of novel spherical flame retardant Co-MOF carbonizing agent and epoxy modified tannic acid with polyester material makes up for the defect of poor compatibility of ammonium polyphosphate, so that the flame retardant polyester composite material has relatively good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 is the flame retardant organic ligand in Example 1 1 H NMR spectrum.
[0041] Figure 2 This is the infrared spectrum of the epoxy-modified tannic acid in Example 1. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0043] Example 1
[0044] A method for preparing a flame retardant and anti-melting droplet bio-polyester material comprises the following steps:
[0045] (1) First, under a nitrogen atmosphere, 0.04 mol 4-formylbenzoic acid and 1 mL glacial acetic acid were dissolved in 100 mL anhydrous ethanol, and then 50 mL anhydrous ethanol solution containing 0.02 mol p-phenylenediamine was added dropwise to the above system at 70°C. After reacting for 8 hours, 0.04 mol DOPO was added to the above system while keeping the temperature unchanged. After continuing the reaction for 12 hours, a light yellow precipitate was obtained by centrifugation, and then washed with anhydrous ethanol and centrifuged 3 times. Finally, it was dried in a vacuum oven at 60°C for 12 hours to obtain a flame retardant organic ligand.
[0046] Its NMR spectrum is as follows Figure 1 As shown by Figure 1 It can be seen that the peaks at 12.8ppm, 8.2ppm and 7.1ppm are the flame retardant organic ligand proton signal peaks g, f and e, while the multiple peaks at 8.0-7.0ppm correspond to the proton peak d, and the proton peaks at 6.3ppm, 6.0ppm and 5.0ppm correspond to the flame retardant organic ligand proton signal peaks a, b and c respectively;
[0047] (2) 2.412 g (0.003 mol) of flame-retardant organic ligand was dispersed in 100 mL of anhydrous methanol, 1 mL of ammonia water (0.93 g) was added and stirred for 10 min to obtain a uniform solution, 50 mL of methanol solution containing 0.582 g (0.002 mol) of cobalt nitrate hexahydrate was added dropwise to the above system, stirred for 10 min and then transferred to a high-pressure reactor, and a solvent thermal reaction was carried out at 160 ° C for 48 h. After the reaction was completed, it was cooled to room temperature and centrifuged to obtain a green precipitate, which was then washed with anhydrous methanol for 3 times and finally dried in a vacuum oven at 80 ° C for 24 h to obtain a flame-retardant Co-MOF carbonizer;
[0048] (3) Under a nitrogen atmosphere, 8.505 g (0.005 mol) of tannic acid was dissolved in 173.438 g (1.875 mol) of epichlorohydrin, 1.82 g of tetrabutylammonium bromide was added, the mixture was reacted at 80° C. for 3 h, the temperature was lowered to 50° C., 16 g (30 wt %) of sodium hydroxide aqueous solution was added, and the reaction was continued for 6 h. After the reaction was completed, the mixture was washed with deionized water 5 times and separated, and then rotary evaporated at 80° C. to obtain a viscous brown liquid, which was finally dried in a vacuum oven at 80° C. for 24 h to obtain epoxy-modified tannic acid;
[0049] Its infrared spectrum is as follows Figure 2 As shown by Figure 2 It can be seen that tannic acid (TA) is at 2800-3700 cm -1 The broad peak in the range is the vibration absorption peak of phenolic hydroxyl group (Ar-OH), while the peak at 1698 cm-1 The absorption peak at is the absorption peak of the C=O bond in TA. From the curve of epoxy-modified tannic acid (eTA), it can be seen that the broad peak of phenolic hydroxyl group basically disappears, and the absorption peak of C=O bond shifts to 1710cm -1 At 2800-3000cm -1 The CH bond absorption peak appears in the range and at 905cm -1 The epoxy peak appears at , proving that the phenolic hydroxyl group in TA reacts with epichlorohydrin;
[0050] (4) 4 parts by mass of flame-retardant Co-MOF carbonizer, 4 parts by mass of ammonium polyphosphate and 10 parts by mass of epoxy-modified tannic acid are melt-blended with 82 parts by mass of polylactic acid (PLA) at 185°C for 6 minutes using a torque rheometer, and then a flame-retardant and anti-drip biopolyester material is obtained through a molding process.
[0051] Example 2
[0052] A method for preparing a flame retardant and anti-melting droplet bio-polyester material comprises the following steps:
[0053] (1) First, under a nitrogen atmosphere, 0.04 mol 4-formylbenzoic acid and 1 mL glacial acetic acid were dissolved in 100 mL anhydrous ethanol, and then 50 mL anhydrous ethanol solution containing 0.02 mol p-phenylenediamine was added dropwise to the above system at 70°C. After reacting for 8 hours, 0.04 mol DOPO was added to the above system while keeping the temperature unchanged. After continuing the reaction for 12 hours, a light yellow precipitate was obtained by centrifugation, and then washed with anhydrous ethanol and centrifuged 3 times. Finally, it was dried in a vacuum oven at 60°C for 12 hours to obtain a flame retardant organic ligand.
[0054] (2) 2.412 g (0.003 mol) of flame-retardant organic ligand was dispersed in 100 mL of anhydrous methanol, 1 mL of ammonia water (0.93 g) was added and stirred for 10 min to obtain a uniform solution, 50 mL of methanol solution containing 0.582 g (0.002 mol) of cobalt nitrate hexahydrate was added dropwise to the above system, stirred for 10 min and then transferred to a high-pressure reactor, and a solvent thermal reaction was carried out at 160 ° C for 48 h. After the reaction was completed, it was cooled to room temperature and centrifuged to obtain a green precipitate, which was then washed with anhydrous methanol for 3 times and finally dried in a vacuum oven at 80 ° C for 24 h to obtain a flame-retardant Co-MOF carbonizer;
[0055] (3) Under a nitrogen atmosphere, 8.505 g (0.005 mol) of tannic acid was dissolved in 173.438 g (1.875 mol) of epichlorohydrin, 1.82 g of tetrabutylammonium bromide was added, the mixture was reacted at 80° C. for 3 h, the temperature was lowered to 50° C., 16 g (30 wt %) of sodium hydroxide aqueous solution was added, and the reaction was continued for 6 h. After the reaction was completed, the mixture was washed with deionized water 5 times and separated, and then rotary evaporated at 80° C. to obtain a viscous brown liquid, which was finally dried in a vacuum oven at 80° C. for 24 h to obtain epoxy-modified tannic acid;
[0056] (4) 5 parts by mass of flame-retardant Co-MOF carbonizer, 5 parts by mass of ammonium polyphosphate and 10 parts by mass of epoxy-modified tannic acid were melt-blended with 80 parts by mass of polylactic acid (PLA) at 185°C for 7 minutes using a torque rheometer, and then a flame-retardant and anti-drip biopolyester material was obtained through a molding process.
[0057] Example 3
[0058] A method for preparing a flame retardant and anti-melting droplet bio-polyester material comprises the following steps:
[0059] (1) First, under a nitrogen atmosphere, 0.04 mol 4-formylbenzoic acid and 1 mL glacial acetic acid were dissolved in 100 mL anhydrous ethanol, and then 50 mL anhydrous ethanol solution containing 0.02 mol p-phenylenediamine was added dropwise to the above system at 70°C. After reacting for 8 hours, 0.04 mol DOPO was added to the above system while keeping the temperature unchanged. After continuing the reaction for 12 hours, a light yellow precipitate was obtained by centrifugation, and then washed with anhydrous ethanol and centrifuged 3 times. Finally, it was dried in a vacuum oven at 60°C for 12 hours to obtain a flame retardant organic ligand.
[0060] (2) 2.412 g (0.003 mol) of flame-retardant organic ligand was dispersed in 100 mL of anhydrous methanol, 1 mL of ammonia water (0.93 g) was added and stirred for 10 min to obtain a uniform solution, 50 mL of methanol solution containing 0.582 g (0.002 mol) of cobalt nitrate hexahydrate was added dropwise to the above system, stirred for 10 min and then transferred to a high-pressure reactor, and a solvent thermal reaction was carried out at 160 ° C for 48 h. After the reaction was completed, it was cooled to room temperature and centrifuged to obtain a green precipitate, which was then washed with anhydrous methanol for 3 times and finally dried in a vacuum oven at 80 ° C for 24 h to obtain a flame-retardant Co-MOF carbonizer;
[0061] (3) Under a nitrogen atmosphere, 8.505 g (0.005 mol) of tannic acid was dissolved in 173.438 g (1.875 mol) of epichlorohydrin, 1.82 g of tetrabutylammonium bromide was added, the mixture was reacted at 80° C. for 3 h, the temperature was lowered to 50° C., 16 g (30 wt %) of sodium hydroxide aqueous solution was added, and the reaction was continued for 6 h. After the reaction was completed, the mixture was washed with deionized water 5 times and separated, and then rotary evaporated at 80° C. to obtain a viscous brown liquid, which was finally dried in a vacuum oven at 80° C. for 24 h to obtain epoxy-modified tannic acid;
[0062] (4) 6 parts by mass of flame-retardant Co-MOF carbonizer, 6 parts by mass of ammonium polyphosphate and 10 parts by mass of epoxy-modified tannic acid were melt-blended with 78 parts by mass of PLA at 185°C for 8 minutes using a torque rheometer, and then a flame-retardant and anti-drip biopolyester material was obtained through a molding process.
[0063] Example 4
[0064] A method for preparing a flame retardant and anti-melting droplet bio-polyester material comprises the following steps:
[0065] (1) First, under a nitrogen atmosphere, 0.04 mol 4-formylbenzoic acid and 1 mL glacial acetic acid were dissolved in 100 mL anhydrous ethanol, and then 50 mL anhydrous ethanol solution containing 0.02 mol p-phenylenediamine was added dropwise to the above system at 70°C. After reacting for 8 hours, 0.04 mol DOPO was added to the above system while keeping the temperature unchanged. After continuing the reaction for 12 hours, a light yellow precipitate was obtained by centrifugation, and then washed with anhydrous ethanol and centrifuged 3 times. Finally, it was dried in a vacuum oven at 60°C for 12 hours to obtain a flame retardant organic ligand.
[0066] (2) 2.412 g (0.003 mol) of flame-retardant organic ligand was dispersed in 100 mL of anhydrous methanol, 1 mL of ammonia water (0.93 g) was added and stirred for 10 min to obtain a uniform solution, 50 mL of methanol solution containing 0.582 g (0.002 mol) of cobalt nitrate hexahydrate was added dropwise to the above system, stirred for 10 min and then transferred to a high-pressure reactor, and a solvent thermal reaction was carried out at 160 ° C for 48 h. After the reaction was completed, it was cooled to room temperature and centrifuged to obtain a green precipitate, which was then washed with anhydrous methanol for 3 times and finally dried in a vacuum oven at 80 ° C for 24 h to obtain a flame-retardant Co-MOF carbonizer;
[0067] (3) Under a nitrogen atmosphere, 8.505 g (0.005 mol) of tannic acid was dissolved in 173.438 g (1.875 mol) of epichlorohydrin, 1.82 g of tetrabutylammonium bromide was added, the mixture was reacted at 80° C. for 3 h, the temperature was lowered to 50° C., 16 g (30 wt %) of sodium hydroxide aqueous solution was added, and the reaction was continued for 6 h. After the reaction was completed, the mixture was washed with deionized water 5 times and separated, and then rotary evaporated at 80° C. to obtain a viscous brown liquid, which was finally dried in a vacuum oven at 80° C. for 24 h to obtain epoxy-modified tannic acid;
[0068] (4) 5 parts by mass of flame-retardant Co-MOF carbonizer, 5 parts by mass of ammonium polyphosphate and 15 parts by mass of epoxy-modified tannic acid were melt-blended with 75 parts by mass of PLA at 185°C for 7 minutes using a torque rheometer, and then a flame-retardant and anti-drip biopolyester material was obtained through a molding process.
[0069] Example 5
[0070] A method for preparing a flame retardant and anti-melting droplet bio-polyester material comprises the following steps:
[0071] (1) First, under a nitrogen atmosphere, 0.04 mol 4-formylbenzoic acid and 1 mL glacial acetic acid were dissolved in 100 mL anhydrous ethanol, and then 50 mL anhydrous ethanol solution containing 0.02 mol p-phenylenediamine was added dropwise to the above system at 70°C. After reacting for 8 hours, 0.04 mol DOPO was added to the above system while keeping the temperature unchanged. After continuing the reaction for 12 hours, a light yellow precipitate was obtained by centrifugation, and then washed with anhydrous ethanol and centrifuged 3 times. Finally, it was dried in a vacuum oven at 60°C for 12 hours to obtain a flame retardant organic ligand.
[0072] (2) 2.412 g (0.003 mol) of flame-retardant organic ligand was dispersed in 100 mL of anhydrous methanol, 1 mL of ammonia water (0.93 g) was added and stirred for 10 min to obtain a uniform solution, 50 mL of methanol solution containing 0.582 g (0.002 mol) of cobalt nitrate hexahydrate was added dropwise to the above system, stirred for 10 min and then transferred to a high-pressure reactor, and a solvent thermal reaction was carried out at 160 ° C for 48 h. After the reaction was completed, it was cooled to room temperature and centrifuged to obtain a green precipitate, which was then washed with anhydrous methanol for 3 times and finally dried in a vacuum oven at 80 ° C for 24 h to obtain a flame-retardant Co-MOF carbonizer;
[0073] (3) Under a nitrogen atmosphere, 8.505 g (0.005 mol) of tannic acid was dissolved in 173.438 g (1.875 mol) of epichlorohydrin, 1.82 g of tetrabutylammonium bromide was added, the mixture was reacted at 80° C. for 3 h, the temperature was lowered to 50° C., 16 g (30 wt %) of sodium hydroxide aqueous solution was added, and the reaction was continued for 6 h. After the reaction was completed, the mixture was washed with deionized water 5 times and separated, and then rotary evaporated at 80° C. to obtain a viscous brown liquid, which was finally dried in a vacuum oven at 80° C. for 24 h to obtain epoxy-modified tannic acid;
[0074] (4) 6 parts by mass of flame-retardant Co-MOF carbonizer, 6 parts by mass of ammonium polyphosphate and 15 parts by mass of epoxy-modified tannic acid were melt-blended with 73 parts by mass of PLA at 185°C for 7 minutes using a torque rheometer, and then a flame-retardant and anti-drip biopolyester material was obtained through a molding process.
[0075] Example 6
[0076] A method for preparing a flame retardant and anti-melting droplet bio-polyester material comprises the following steps:
[0077] (1) First, under a nitrogen atmosphere, 0.04 mol 4-formylbenzoic acid and 1 mL glacial acetic acid were dissolved in 100 mL anhydrous ethanol, and then 50 mL anhydrous ethanol solution containing 0.02 mol p-phenylenediamine was added dropwise to the above system at 70°C. After reacting for 8 h, 0.04 mol DOPO was added to the above system while keeping the temperature unchanged. After continuing the reaction for 12 h, a light yellow precipitate was obtained by centrifugation, which was then washed with anhydrous ethanol and centrifuged three times. Finally, it was dried in a vacuum oven at 60°C for 12 h to obtain a flame retardant organic ligand.
[0078] (2) 2.412 g (0.003 mol) of flame-retardant organic ligand was dispersed in 100 mL of anhydrous methanol, 1 mL of ammonia water (0.93 g) was added and stirred for 10 min to obtain a uniform solution, 50 mL of methanol solution containing 0.582 g (0.002 mol) of cobalt nitrate hexahydrate was added dropwise to the above system, stirred for 10 min and then transferred to a high-pressure reactor, and a solvent thermal reaction was carried out at 160 ° C for 48 h. After the reaction was completed, it was cooled to room temperature and centrifuged to obtain a green precipitate, which was then washed with anhydrous methanol for 3 times and finally dried in a vacuum oven at 80 ° C for 24 h to obtain a flame-retardant Co-MOF carbonizer;
[0079] (3) Under a nitrogen atmosphere, 8.505 g (0.005 mol) of tannic acid was dissolved in 173.438 g (1.875 mol) of epichlorohydrin, 1.82 g of tetrabutylammonium bromide was added, the mixture was reacted at 80° C. for 3 h, the temperature was lowered to 50° C., 16 g (30 wt %) of sodium hydroxide aqueous solution was added, and the reaction was continued for 6 h. After the reaction was completed, the mixture was washed with deionized water 5 times and separated, and then rotary evaporated at 80° C. to obtain a viscous brown liquid, which was finally dried in a vacuum oven at 80° C. for 24 h to obtain epoxy-modified tannic acid;
[0080] (4) 5 parts by mass of flame-retardant Co-MOF carbonizer, 5 parts by mass of ammonium polyphosphate and 15 parts by mass of epoxy-modified tannic acid were melt-blended with 75 parts by mass of PGA at 240°C for 8 minutes using a torque rheometer, and then a flame-retardant and anti-drip biopolyester material was obtained through a molding process.
[0081] Example 7
[0082] A method for preparing a flame retardant and anti-melting droplet bio-polyester material comprises the following steps:
[0083] (1) First, under a nitrogen atmosphere, 0.04 mol 4-formylbenzoic acid and 1 mL glacial acetic acid were dissolved in 100 mL anhydrous ethanol, and then 50 mL anhydrous ethanol solution containing 0.02 mol p-phenylenediamine was added dropwise to the above system at 70°C. After reacting for 8 hours, 0.04 mol DOPO was added to the above system while keeping the temperature unchanged. After continuing the reaction for 12 hours, a light yellow precipitate was obtained by centrifugation, and then washed with anhydrous ethanol and centrifuged 3 times. Finally, it was dried in a vacuum oven at 60°C for 12 hours to obtain a flame retardant organic ligand.
[0084] (2) 2.412 g (0.003 mol) of flame-retardant organic ligand was dispersed in 100 mL of anhydrous methanol, 1 mL of ammonia water (0.93 g) was added and stirred for 10 min to obtain a uniform solution, 50 mL of methanol solution containing 0.582 g (0.002 mol) of cobalt nitrate hexahydrate was added dropwise to the above system, stirred for 10 min and then transferred to a high-pressure reactor, and solvent thermal reaction was carried out at 160 ° C for 48 h. After the reaction was completed, it was cooled to room temperature and centrifuged to obtain a green precipitate, which was then washed with anhydrous methanol for 3 times and finally dried in a vacuum oven at 80 ° C for 24 h to obtain a flame-retardant Co-MOF carbonizer;
[0085] (3) Under a nitrogen atmosphere, 8.505 g (0.005 mol) of tannic acid was dissolved in 173.438 g (1.875 mol) of epichlorohydrin, 1.82 g of tetrabutylammonium bromide was added, the mixture was reacted at 80° C. for 3 h, the temperature was lowered to 50° C., 16 g (30 wt %) of sodium hydroxide aqueous solution was added, and the reaction was continued for 6 h. After the reaction was completed, the mixture was washed with deionized water 5 times and separated, and then rotary evaporated at 80° C. to obtain a viscous brown liquid, which was finally dried in a vacuum oven at 80° C. for 24 h to obtain epoxy-modified tannic acid;
[0086] (4) 5 parts by mass of flame-retardant Co-MOF carbonizer, 5 parts by mass of ammonium polyphosphate and 15 parts by mass of epoxy-modified tannic acid were melt-blended with 75 parts by mass of PHA at 165°C for 6 minutes using a torque rheometer, and then a flame-retardant and anti-drip biopolyester material was obtained through a molding process.
[0087] Example 8
[0088] A method for preparing a flame retardant and anti-melting droplet bio-polyester material comprises the following steps:
[0089] (1) First, under a nitrogen atmosphere, 0.04 mol 4-formylbenzoic acid and 1 mL glacial acetic acid were dissolved in 100 mL anhydrous ethanol, and then 50 mL anhydrous ethanol solution containing 0.02 mol p-phenylenediamine was added dropwise to the above system at 70°C. After reacting for 8 h, 0.04 mol DOPO was added to the above system while keeping the temperature unchanged. After continuing the reaction for 12 h, a light yellow precipitate was obtained by centrifugation, which was then washed with anhydrous ethanol and centrifuged three times. Finally, it was dried in a vacuum oven at 60°C for 12 h to obtain a flame retardant organic ligand.
[0090] (2) 2.412 g (0.003 mol) of flame-retardant organic ligand was dispersed in 100 mL of anhydrous methanol, 1 mL of ammonia water (0.93 g) was added and stirred for 10 min to obtain a uniform solution, 50 mL of methanol solution containing 0.582 g (0.002 mol) of cobalt nitrate hexahydrate was added dropwise to the above system, stirred for 10 min and then transferred to a high-pressure reactor, and a solvent thermal reaction was carried out at 160 ° C for 48 h. After the reaction was completed, it was cooled to room temperature and centrifuged to obtain a green precipitate, which was then washed with anhydrous methanol for 3 times and finally dried in a vacuum oven at 80 ° C for 24 h to obtain a flame-retardant Co-MOF carbonizer;
[0091] (3) Under a nitrogen atmosphere, 8.505 g (0.005 mol) of tannic acid was dissolved in 173.438 g (1.875 mol) of epichlorohydrin, 1.82 g of tetrabutylammonium bromide was added, the mixture was reacted at 80° C. for 3 h, the temperature was lowered to 50° C., 16 g (30 wt %) of sodium hydroxide aqueous solution was added, and the reaction was continued for 6 h. After the reaction was completed, the mixture was washed with deionized water 5 times and separated, and then rotary evaporated at 80° C. to obtain a viscous brown liquid, which was finally dried in a vacuum oven at 80° C. for 24 h to obtain epoxy-modified tannic acid;
[0092] (4) 5 parts by mass of flame-retardant Co-MOF carbonizer, 5 parts by mass of ammonium polyphosphate and 15 parts by mass of epoxy-modified tannic acid were melt-blended with 75 parts by mass of PBS at 140°C for 7 minutes using a torque rheometer, and then a flame-retardant and anti-drip biopolyester material was obtained through a molding process.
[0093] Example 9
[0094] A method for preparing a flame retardant and anti-melting droplet bio-polyester material comprises the following steps:
[0095] (1) First, under a nitrogen atmosphere, 0.044 mol of 4-formylbenzoic acid and 1 mL of glacial acetic acid were dissolved in 100 mL of anhydrous ethanol, and then 50 mL of anhydrous ethanol solution containing 0.02 mol of p-phenylenediamine was added dropwise to the above system at 70°C. After reacting for 8 h, 0.044 mol of DOPO was added to the above system while keeping the temperature unchanged. After continuing the reaction for 12 h, a light yellow precipitate was obtained by centrifugation, which was then washed with anhydrous ethanol and centrifuged three times. Finally, it was dried in a vacuum oven at 60°C for 12 h to obtain a flame retardant organic ligand.
[0096] (2) 2.412 g (0.003 mol) of flame-retardant organic ligand was dispersed in 100 mL of anhydrous methanol, 1 mL of ammonia water (0.93 g) was added and stirred for 10 min to obtain a uniform solution, 50 mL of methanol solution containing 0.291 g (0.001 mol) of cobalt nitrate hexahydrate was added dropwise to the above system, stirred for 10 min and then transferred to a high-pressure reactor, and a solvent thermal reaction was carried out at 160 ° C for 48 h. After the reaction was completed, it was cooled to room temperature and centrifuged to obtain a green precipitate, which was then washed with anhydrous methanol for 3 times and finally dried in a vacuum oven at 80 ° C for 24 h to obtain a flame-retardant Co-MOF carbonizer;
[0097] (3) Under a nitrogen atmosphere, 8.505 g (0.005 mol) of tannic acid was dissolved in 173.438 g (1.875 mol) of epichlorohydrin, 1.82 g of tetrabutylammonium bromide was added, the mixture was reacted at 80° C. for 3 h, the temperature was lowered to 50° C., 16 g (30 wt %) of sodium hydroxide aqueous solution was added, and the reaction was continued for 6 h. After the reaction was completed, the mixture was washed with deionized water 5 times and separated, and then rotary evaporated at 80° C. to obtain a viscous brown liquid, which was finally dried in a vacuum oven at 80° C. for 24 h to obtain epoxy-modified tannic acid;
[0098] (4) 4 parts by mass of flame-retardant Co-MOF carbonizer, 4 parts by mass of ammonium polyphosphate and 10 parts by mass of epoxy-modified tannic acid are melt-blended with 82 parts by mass of polylactic acid (PLA) at 185°C for 6 minutes using a torque rheometer, and then a flame-retardant and anti-drip biopolyester material is obtained through a molding process.
[0099] Example 10
[0100] A method for preparing a flame retardant and anti-melting droplet bio-polyester material comprises the following steps:
[0101] (1) First, under a nitrogen atmosphere, 0.044 mol of 4-formylbenzoic acid and 1 mL of glacial acetic acid were dissolved in 100 mL of anhydrous ethanol, and then 50 mL of anhydrous ethanol solution containing 0.02 mol of p-phenylenediamine was added dropwise to the above system at 70°C. After reacting for 8 h, 0.044 mol of DOPO was added to the above system while keeping the temperature unchanged. After continuing the reaction for 12 h, a light yellow precipitate was obtained by centrifugation, which was then washed with anhydrous ethanol and centrifuged three times. Finally, it was dried in a vacuum oven at 60°C for 12 h to obtain a flame retardant organic ligand.
[0102] (2) 2.412 g (0.003 mol) of flame-retardant organic ligand was dispersed in 100 mL of anhydrous methanol, 1 mL of ammonia water (0.93 g) was added and stirred for 10 min to obtain a uniform solution, 50 mL of methanol solution containing 0.291 g (0.001 mol) of cobalt nitrate hexahydrate was added dropwise to the above system, stirred for 10 min and then transferred to a high-pressure reactor, and a solvent thermal reaction was carried out at 160 ° C for 48 h. After the reaction was completed, it was cooled to room temperature and centrifuged to obtain a green precipitate, which was then washed with anhydrous methanol for 3 times and finally dried in a vacuum oven at 80 ° C for 24 h to obtain a flame-retardant Co-MOF carbonizer;
[0103] (3) Under a nitrogen atmosphere, 8.505 g (0.005 mol) of tannic acid was dissolved in 115.668 g (1.25 mol) of epichlorohydrin, 1.24 g of tetrabutylammonium bromide was added, the mixture was reacted at 80° C. for 3 h, the temperature was lowered to 50° C., 16 g (30 wt%) of sodium hydroxide aqueous solution was added, and the reaction was continued for 6 h. After the reaction was completed, the mixture was washed with deionized water 5 times and separated, and then rotary evaporated at 80° C. to obtain a viscous brown liquid, which was finally dried in a vacuum oven at 80° C. for 24 h to obtain epoxy-modified tannic acid;
[0104] (4) 4 parts by mass of flame-retardant Co-MOF carbonizer, 4 parts by mass of ammonium polyphosphate and 10 parts by mass of epoxy-modified tannic acid are melt-blended with 82 parts by mass of polylactic acid (PLA) at 185°C for 6 minutes using a torque rheometer, and then a flame-retardant and anti-drip biopolyester material is obtained through a molding process.
[0105] Comparative Example 1
[0106] A method for preparing a bio-polyester material, comprising the following steps: (same as Example 1, except that no flame retardant is added)
[0107] 100 parts by mass of PLA were melt-blended at 185° C. for 7 minutes using a torque rheometer, and then a polyester material was obtained through a molding process.
[0108] Comparative Example 2
[0109] A method for preparing a biopolyester material, comprising the following steps: (same as Example 2, except that Co-MOF is not added)
[0110] 5 parts by mass of ammonium polyphosphate and 10 parts by mass of epoxy-modified tannic acid are melt-blended with 85 parts by mass of PLA at 185° C. for 7 minutes using a torque rheometer, and then a polyester material is obtained through a molding process.
[0111] Comparative Example 3
[0112] A method for preparing a bio-polyester material comprises the following steps: (same as Example 2, except that epoxy-modified tannic acid is not added)
[0113] 5 parts by mass of flame-retardant Co-MOF carbonizer and 5 parts by mass of ammonium polyphosphate were melt-blended with 90 parts by mass of PLA at 185° C. for 7 minutes using a torque rheometer, and then a polyester material was obtained through a molding process.
[0114] Comparative Example 4
[0115] A method for preparing a bio-polyester material comprises the following steps: (same as Example 2, except that ammonium polyphosphate is not added)
[0116] 5 parts by mass of flame retardant Co-MO carbonizer F and 10 parts by mass of epoxy modified tannic acid are melt-blended with 85 parts by mass of PLA at 185° C. for 7 minutes by means of a torque rheometer, and then a polyester material is obtained by a molding process.
[0117] Comparative Example 5
[0118] A method for preparing a biopolyester material comprises the following steps: (Compared with Example 2, DOPO and epoxy-modified tannic acid are directly added)
[0119] (1) Under a nitrogen atmosphere, 8.505 g (0.005 mol) of tannic acid was dissolved in 173.438 g (1.875 mol) of epichlorohydrin, 1.82 g of tetrabutylammonium bromide was added, the mixture was reacted at 80° C. for 3 h, the temperature was lowered to 50° C., 16 g (30 wt%) of sodium hydroxide aqueous solution was added, and the reaction was continued for 6 h. After the reaction was completed, the mixture was washed with deionized water for 5 times, and then rotary evaporated at 80° C. to obtain a viscous brown liquid, which was finally dried in a vacuum oven at 80° C. for 24 h to obtain epoxy-modified tannic acid;
[0120] (2) 5 parts by mass of DOPO and 10 parts by mass of epoxy-modified tannic acid are melt-blended with 85 parts by mass of PLA using a torque rheometer at 185° C. for 7 minutes, and then a polyester material is obtained through a molding process.
[0121] Comparative Example 6
[0122] A method for preparing a bio-polyester material, comprising the following steps: (same as Example 6, except that no flame retardant is added)
[0123] 100 parts by mass of PGA were melt-blended at 240° C. for 8 minutes using a torque rheometer, and then a polyester material was obtained through a molding process.
[0124] Comparative Example 7
[0125] A method for preparing a bio-polyester material, comprising the following steps: (same as Example 7, except that no flame retardant is added)
[0126] 100 parts by mass of PHA were melt-blended at 165° C. for 6 minutes using a torque rheometer, and then a polyester material was obtained through a molding process.
[0127] Comparative Example 8
[0128] A method for preparing a bio-polyester material, comprising the following steps: (same as Example 8, except that no flame retardant is added)
[0129] 100 parts by mass of PBS were melt-blended at 140° C. for 7 minutes using a torque rheometer, and then a polyester material was obtained through a molding process.
[0130] Test example:
[0131] The flame retardant properties and mechanical properties of Examples 1-8 and Comparative Examples 1-8 were tested, and the test results are shown in Table 1.
[0132] Table 1
[0133] project LOI(%) UL-94 Droplets Tensile strength(MPa) UPF Example 1 27.0 V-0 none 64 1725 Example 2 28.3 V-0 none 65 1856 Example 3 29.2 V-0 none 63 2036 Example 4 28.8 V-0 none 66 2156 Example 5 29.6 V-0 none 65 2114 Example 6 27.3 V-0 none 112 1869 Example 7 27.1 V-0 none 23 1989 Example 8 28.1 V-0 none 24 1925 Example 9 26.4 V-0 none 65 1755 Example 10 26.8 V-0 none 63 1719 Comparative Example 1 19.5 NR have 67 1 Comparative Example 2 25.2 V-2 have 60 531 Comparative Example 3 27.1 V-0 have 62 158 Comparative Example 4 26.3 V-2 have 68 1555 Comparative Example 5 25.0 V-2 have 52 1454 Comparative Example 6 22.0 NR have 115 2 Comparative Example 7 20.5 NR have 23 1 Comparative Example 8 21.0 NR have 26 14
[0134] Note: The limiting oxygen index (LOI) of the material is tested according to GBT2406.2-2009 standard; the vertical combustion (UL-94) test is carried out on the material according to ASTM D3801 standard; the tensile strength of the material is tested according to GB / T 1040-2006, and the tensile rate is 10mm / min; the ultraviolet protection factor (UPF) is calculated according to the ultraviolet transmittance of polyester material in the range of 290nm-400nm
[0135] From the data in Table 1, it can be seen that PLA (Comparative Example 1) is extremely flammable, with an LOI of only 19.5%. At the same time, it has no UL-94 grade and has a serious droplet problem during the combustion process. PGA (Comparative Example 6), PHA (Comparative Example 7) and PBS (Comparative Example 8) are also extremely flammable. Although adding any two flame retardant components of flame retardant Co-MOF, epoxy-modified tannic acid and ammonium polyphosphate can improve the LOI value and UL-94 grade of polyester materials, it cannot solve the existing droplet problem. This may be because one or two flame retardant components alone cannot effectively exert an efficient flame retardant effect in the gas phase and condensation phase at the same time, and cannot interrupt the chain reaction of combustion or form a continuous and dense protective carbon layer to block the combustion reaction. The use of flame retardant Co-MOF, epoxy-modified tannic acid and ammonium polyphosphate together has a synergistic carbonization effect, forming a continuous and dense protective carbon layer during the combustion process, and the generated inert gas can expand the carbon layer, thereby limiting the transfer of heat and oxygen, better protecting the polyester material matrix, and effectively inhibiting the melt dripping of the polyester material.
[0136] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A flame retardant and anti-drip biopolyester material, characterized in that: The raw materials include 73-82wt% polyester material and 18-27wt% composite flame retardant; The composite flame retardant is composed of Co-MOF carbonizing agent, epoxy-modified tannic acid and ammonium polyphosphate; The preparation method of the Co-MOF carbonizer is as follows: 4-formylbenzoic acid, p-phenylenediamine and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide react to generate a flame retardant organic ligand, and then react with a cobalt salt to obtain the carbonizer by solvent thermal reaction; The epoxy-modified tannic acid is prepared by reacting epichlorohydrin with tannic acid; the mass ratio of tannic acid to epichlorohydrin is 1:13.6-27.2; The proportions of Co-MOF carbonizer, epoxy-modified tannic acid and ammonium polyphosphate in the raw materials are 4-6wt%, 10-15wt% and 4-6wt%, respectively.
2. The flame retardant and anti-drip biopolyester material according to claim 1, characterized in that: The polyester material is one or more of polylactic acid, polyglycolic acid, polyhydroxyalkanoate, and polybutylene succinate.
3. The flame retardant and anti-drip biopolyester material according to claim 1, characterized in that: The molar ratio of the 4-formylbenzoic acid, p-phenylenediamine and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 2-2.4:1:2-2.
4.
4. The flame retardant and anti-drip biopolyester material according to claim 1, characterized in that: The cobalt salt is cobalt nitrate hexahydrate; the molar ratio of the flame retardant organic ligand to the cobalt nitrate hexahydrate is 3:1-2.
5. A method for preparing the flame retardant and anti-drip biopolyester material according to claim 1, characterized in that: The preparation method comprises the following steps: 73-82 wt% of polyester material and 18-27 wt% of composite flame retardant are added into a screw extruder or a torque rheometer for melt blending, and then a flame retardant and anti-melting droplet bio-polyester material is obtained through a molding process.
6. The preparation method according to claim 5, characterized in that: The temperature of melt blending is 140-240°C and the time is 6-10 minutes.
7. An application of the flame retardant and anti-drip biopolyester material according to claim 1, characterized in that: Used in textile, transportation or electronic and electrical fields.
8. The use according to claim 7, characterized in that: Used in the automotive field.
Citation Information
Patent Citations
Flame-retardant polyethylene glycol terephthalate composite material as well as preparation method and application thereof
CN116063831A
Preparation method of flame-retardant polyester
CN116855041A